A method for preparing high-strength modified engineering plastics

By optimizing the formulation and process in a high mixer and adding reinforcing fibers, the problems of degradation of mechanical properties and prone to cracking in traditional engineering plastics are solved, and the tensile strength and bending strength of modified engineering plastics are significantly improved.

CN118480260BActive Publication Date: 2025-03-11清远市庆鸿塑料有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410856029.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2025-03-11
Estimated Expiration
2044-06-28

AI Technical Summary

Technical Problem

Traditional engineering plastics have problems of degraded mechanical properties and prone to cracking in certain specific applications, making it difficult to meet the needs of high strength and durability.

Method used

By optimizing the formulation and process in the high-mixer, 50-70 parts of matrix resin, 3-10 parts of toughening agent, 0.5-2 parts of antioxidant, 0.5-2 parts of lubricant and 0.5-3 parts of plasticizer, and 10-30 parts of reinforcing fibers were added to the twin-screw extruder to prepare high-strength modified engineering plastic.

Benefits of technology

It improves the tensile strength and bending strength of modified engineering plastics, extends the service life of the material and expands its application range.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for preparing high-strength modified engineering plastics, and relates to the technical field of engineering plastics. The method comprises the following specific steps: adding a matrix resin, a toughening agent, an antioxidant, a lubricant and a plasticizer into a high-speed mixer, preliminarily mixing, stopping the mixer to add reinforcing fibers, continuing to mix, extruding the mixture through a twin-screw extruder, cooling and cutting into particles to obtain the modified engineering plastics. The method improves the mechanical strength of engineering plastics by optimizing the formula and processing technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of engineering plastics, and in particular to a method for preparing high-strength modified engineering plastics. Background Art

[0002] Modified engineering plastics are plastic materials that are made by adding various modifiers such as reinforcing fibers, toughening agents, antioxidants, lubricants and plasticizers to the base resin to improve the comprehensive properties of the material so that it can meet the needs of specific applications. These modifiers improve the mechanical strength, heat resistance, chemical resistance, toughness and processing properties of the material by changing the internal structure of the material and the interaction of the molecular chains.

[0003] An environmentally friendly high modulus PC modified engineering plastic (Chinese patent application number: CN201310401737.X) is prepared from PC polycarbonate, PC scraps, silicate fibers, phosphate flame retardants, antioxidants, and mold release agents. The environmentally friendly high modulus PC modified engineering plastic of the present invention uses PC scraps, and under the action of polycarbonate, silicate fibers and phosphate flame retardants, the PC scraps are modified and recycled, so that the mechanical properties and flame retardant properties of the PC scraps are greatly improved, thereby effectively recycling the PC scraps.

[0004] A highly weather-resistant and high-rigidity modified engineering plastic and a preparation method thereof (Chinese patent application number: CN202011235810.7) include the following raw materials in parts by weight: 90-100 parts of a polyamide resin, 5-7 parts of a toughening agent, 2-4 parts of a lubricant, 0.6-0.8 parts of modified titanium dioxide and 70-80 parts of a filler; the highly weather-resistant and high-rigidity modified engineering plastic is prepared by the following steps: a first step, weighing the raw materials by weight; a second step, mixing the polyamide resin, the toughening agent and the lubricant, stirring at 45-60°C for 10-15 minutes, and cooling to room temperature to obtain a premix; a third step, adding the modified titanium dioxide and the filler to the premix, stirring at 50-65°C for 15-20 minutes to obtain a mixture, and melt-extruding and granulating the mixture in a single-screw extruder, the extrusion temperature is 220-240°C, and the screw speed is 30-36r / min to obtain a highly weather-resistant and high-rigidity modified engineering plastic.

[0005] An environmentally friendly flame-retardant PC / ABS modified engineering plastic (Chinese patent application number: CN201310401662.5) is prepared from PC polycarbonate, PC / ABS, silicate fibers, phosphate flame retardants, ABS, antioxidants, and mold release agents. The environmentally friendly flame-retardant PC / ABS modified engineering plastic of the present invention uses PC / ABS scraps, and under the action of ABS, polycarbonate, silicate fibers and phosphate flame retardants, the PC / ABS scraps are modified and recycled, so that the mechanical properties and flame retardant properties of the PC / ABS scraps are greatly improved, thereby effectively recycling the PC / ABS scraps.

[0006] New plastic woven bags can also use engineering plastics as the main raw material, through drawing, weaving, printing, sewing and other processes. Plastic woven bags have a wide range of applications. At present, plastic woven bags are mainly used for agricultural product packaging, cement bag packaging, food packaging, geotechnical engineering, tourism transportation, flood control materials, etc.

[0007] Traditional engineering plastics such as polyamide (PA) and polycarbonate (PC), although they have excellent basic properties, still have certain limitations in certain specific applications. For example, polyamide is prone to mechanical property degradation after long-term use; polycarbonate is prone to cracking when impacted. Summary of the invention

[0008] In view of the technical problems raised in the above background technology, the purpose of the present invention is to provide a method for preparing high-strength modified engineering plastics, which improves the mechanical properties of engineering plastics, including tensile strength and flexural strength, by optimizing the formula and process.

[0009] In order to achieve the above-mentioned invention object, this method proposes the following solution:

[0010] A method for preparing high-strength modified engineering plastics, characterized in that it comprises the following steps:

[0011] According to weight parts, 50-70 parts of base resin, 3-10 parts of toughening agent, 0.5-2 parts of antioxidant, 0.5-2 parts of lubricant and 0.5-3 parts of plasticizer are added to a high-speed mixer, and preliminarily mixed for 5-15 minutes. Then, 10-30 parts of reinforcing fiber are added after stopping the machine, and mixing is continued for 15-20 minutes. The mixture is extruded through a twin-screw extruder, cooled and cut into particles to obtain the modified engineering plastic.

[0012] Further preferably, the matrix resin is selected from polyamide or polycarbonate.

[0013] Further preferably, the toughening agent is selected from at least one of ethylene-propylene-diene monomer rubber, styrene-butadiene rubber, butadiene rubber, thermoplastic polyurethane, thermoplastic polyolefin elastomer, and styrene-butadiene-styrene copolymer.

[0014] Further preferably, the antioxidant is selected from at least one of 2,6-di-tert-butyl-4-methylphenol, pentaerythritol tetrakis[(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, bis[3,5-di-tert-butyl-4-hydroxyphenyl]sulfide, and 2,2'-ethylenebis(4,6-di-tert-butylphenol).

[0015] More preferably, the lubricant is selected from at least one of zinc stearate, calcium stearate and magnesium stearate.

[0016] More preferably, the plasticizer is selected from at least one of tri(2-ethylhexyl) phosphate, dioctyl adipate, triethyl citrate, and diisooctyl terephthalate.

[0017] Further preferably, the reinforcing fiber is a modified glass fiber, and the preparation method thereof is:

[0018] Glass fiber pretreatment: First, clean the glass fiber with a mixture of ethanol and water to remove surface impurities;

[0019] First step modification: add 2-5 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane to 1000-1200 parts of ethanol, add 100-170 parts of glass fiber, stir at room temperature for 30-60 minutes, and the siloxane group reacts with the surface hydroxyl group of the glass fiber;

[0020] Second step modification: then add 5-10 parts of bis[4-(3-aminophenoxy)phenyl]ether, 0.03-0.3 parts of trichlorodiethylaminotitanium, 2.2-4.5 parts of 1,5,7-triazabicyclo[4.4.0]dec-5-ene, heat to 60-70°C, and stir for 50-100 minutes;

[0021] Post-treatment: Finally filter and dry to obtain surface-modified glass fiber.

[0022] Further preferably, the twin-screw extrusion temperature is 260-280°C.

[0023] Reaction mechanism:

[0024] 1. Reaction of epoxy group and amino group: The epoxy group (-CHOCH2O-) grafted on the surface of glass fiber can undergo a ring-opening reaction with the amino group (-NH2) in bis[4-(3-aminophenoxy)phenyl]ether. This reaction is carried out under the conditions of heating and the presence of a catalyst. The ring structure of the epoxy group is opened to form a longer chain structure, and the amino group is connected to the surface of the glass fiber through a covalent bond.

[0025] 2. Cross-linking of titanium complexes: As a coupling agent, the multifunctional amino group of trichlorodiethylaminotitanium can react with the epoxy or silanol group (Si-OH) on the surface of glass fiber to form a stable Ti-O-Si bond. This cross-linking not only enhances the surface hardness of glass fiber, but also improves its bonding ability with resin.

[0026] The high-strength modified engineering plastics prepared by the method of the present invention have the following advantages:

[0027] 1. Improve tensile strength: The modified glass fiber forms a stronger chemical bond and physical interlocking between the surface and the resin, so that the composite material can better disperse stress when subjected to external force, reduce material fracture caused by stress concentration, and thus improve the overall tensile strength.

[0028] 2. Enhanced flexural strength: The surface hardness of the modified glass fiber and its bonding strength with the resin are improved, making the composite material more resistant to bending loads. This means that the material can withstand greater deformation without damage in practical applications, extending the service life of the material and expanding its application range. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Example 1

[0030] A method for preparing high-strength modified engineering plastics, characterized in that it comprises the following steps:

[0031] 50 kg of base resin, 3 kg of toughening agent, 0.5 kg of antioxidant, 0.5 kg of lubricant and 0.5 kg of plasticizer were added to a high-speed mixer, and preliminarily mixed for 5 minutes. The machine was stopped and 10 kg of reinforcing fiber was added, and mixing was continued for 15 minutes. The mixture was extruded through a twin-screw extruder, cooled and cut into particles to obtain the modified engineering plastic.

[0032] The base resin is selected from polyamide.

[0033] The toughening agent is selected from ethylene-propylene-diene monomer rubber.

[0034] The antioxidant is selected from 2,6-di-tert-butyl-4-methylphenol.

[0035] The lubricant is selected from zinc stearate.

[0036] The plasticizer is selected from tri(2-ethylhexyl)phosphate.

[0037] The reinforcing fiber is a modified glass fiber, and its preparation method is:

[0038] Glass fiber pretreatment: First, clean the glass fiber with a mixture of ethanol and water to remove surface impurities;

[0039] First step modification: add 2kg of 3-(2,3-epoxypropoxy)propyltrimethoxysilane to 1000kg of ethanol, add 100kg of glass fiber, stir at room temperature for 30min, and the siloxane groups react with the surface hydroxyl groups of the glass fiber;

[0040] Second step modification: then add 5 kg of bis[4-(3-aminophenoxy)phenyl]ether, 0.03 kg of diethylaminotitanium trichloride, and 2.2 kg of 1,5,7-triazabicyclo[4.4.0]dec-5-ene, heat to 60°C, and stir for 50 minutes;

[0041] Post-treatment: Finally filter and dry to obtain surface-modified glass fiber.

[0042] The twin-screw extrusion temperature is 260°C. Example 2

[0043] A method for preparing high-strength modified engineering plastics, characterized in that it comprises the following steps:

[0044] 60 kg of base resin, 5 kg of toughening agent, 1 kg of antioxidant, 1 kg of lubricant and 1.5 kg of plasticizer were added to a high-speed mixer, and preliminarily mixed for 10 minutes. The machine was stopped and 20 kg of reinforcing fiber was added, and mixing was continued for 15 minutes. The mixture was extruded through a twin-screw extruder, cooled and cut into particles to obtain the modified engineering plastic.

[0045] The base resin is selected from polyamide.

[0046] The toughening agent is selected from styrene-butadiene rubber.

[0047] The antioxidant is selected from pentaerythritol tetrakis[(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

[0048] The lubricant is selected from calcium stearate.

[0049] The plasticizer is selected from dioctyl adipate.

[0050] The reinforcing fiber is a modified glass fiber, and its preparation method is:

[0051] Glass fiber pretreatment: First, clean the glass fiber with a mixture of ethanol and water to remove surface impurities;

[0052] First step modification: add 3.5 kg of 3-(2,3-epoxypropoxy)propyltrimethoxysilane to 1100 kg of ethanol, add 125 kg of glass fiber, stir at room temperature for 45 minutes, and the siloxane groups react with the surface hydroxyl groups of the glass fiber;

[0053] Second step modification: then add 6.5 kg of bis[4-(3-aminophenoxy)phenyl]ether, 0.1 kg of diethylaminotitanium trichloride, and 3 kg of 1,5,7-triazabicyclo[4.4.0]dec-5-ene, heat to 65°C, and stir for 65 minutes;

[0054] Post-treatment: Finally filter and dry to obtain surface-modified glass fiber.

[0055] The twin-screw extrusion temperature is 270°C. Example 3

[0056] A method for preparing high-strength modified engineering plastics, characterized in that it comprises the following steps:

[0057] 60 kg of base resin, 8 kg of toughening agent, 1.5 kg of antioxidant, 1.5 kg of lubricant and 2.5 kg of plasticizer were added to a high-speed mixer, and preliminarily mixed for 10 minutes. The machine was stopped and 20 kg of reinforcing fiber was added, and mixing was continued for 20 minutes. The mixture was extruded through a twin-screw extruder, cooled and cut into particles to obtain the modified engineering plastic.

[0058] The base resin is selected from polycarbonate.

[0059] The toughening agent is selected from butadiene rubber.

[0060] The antioxidant is selected from bis[3,5-di-tert-butyl-4-hydroxyphenyl]sulfide.

[0061] The lubricant is selected from magnesium stearate.

[0062] The plasticizer is selected from triethyl citrate.

[0063] The reinforcing fiber is a modified glass fiber, and its preparation method is:

[0064] Glass fiber pretreatment: First, clean the glass fiber with a mixture of ethanol and water to remove surface impurities;

[0065] First step modification: add 4 kg of 3-(2,3-epoxypropoxy)propyltrimethoxysilane to 1100 kg of ethanol, add 150 kg of glass fiber, stir at room temperature for 50 min, and the siloxane groups react with the surface hydroxyl groups of the glass fiber;

[0066] Second step modification: then add 8.5 kg of bis[4-(3-aminophenoxy)phenyl]ether, 0.2 kg of diethylaminotitanium trichloride, and 4 kg of 1,5,7-triazabicyclo[4.4.0]dec-5-ene, heat to 65°C, and stir for 80 minutes;

[0067] Post-treatment: Finally filter and dry to obtain surface-modified glass fiber.

[0068] The twin-screw extrusion temperature is 270°C. Example 4

[0069] A method for preparing high-strength modified engineering plastics, characterized in that it comprises the following steps:

[0070] 70 kg of base resin, 10 kg of toughening agent, 2 kg of antioxidant, 2 kg of lubricant and 3 kg of plasticizer were added to a high-speed mixer, and preliminarily mixed for 15 minutes. The machine was stopped and 30 kg of reinforcing fiber was added, and mixing was continued for 20 minutes. The mixture was extruded through a twin-screw extruder, cooled and cut into particles to obtain the modified engineering plastic.

[0071] The base resin is selected from polycarbonate.

[0072] The toughening agent is selected from styrene-butadiene-styrene copolymer.

[0073] The antioxidant is selected from 2,2'-ethylenebis(4,6-di-tert-butylphenol).

[0074] The lubricant is selected from zinc stearate.

[0075] The plasticizer is selected from diisooctyl terephthalate.

[0076] The reinforcing fiber is a modified glass fiber, and its preparation method is:

[0077] Glass fiber pretreatment: First, clean the glass fiber with a mixture of ethanol and water to remove surface impurities;

[0078] First step modification: add 5kg of 3-(2,3-epoxypropoxy)propyltrimethoxysilane to 1200kg of ethanol, add 170kg of glass fiber, stir at room temperature for 60min, and the siloxane groups react with the surface hydroxyl groups of the glass fiber;

[0079] Second step modification: then add 10 kg of bis[4-(3-aminophenoxy)phenyl]ether, 0.3 kg of diethylaminotitanium trichloride, 4.5 kg of 1,5,7-triazabicyclo[4.4.0]dec-5-ene, heat to 70°C, and stir for 100 minutes;

[0080] Post-treatment: Finally filter and dry to obtain surface-modified glass fiber.

[0081] The twin-screw extrusion temperature is 280°C.

[0082] Comparative Example 1

[0083] As a comparative example of Example 1, this example is the same as Example 1 except that an equal amount of glass fiber is used instead of modified glass fiber.

[0084] Comparative Example 2

[0085] As a comparative example of Example 1, this example is the same as Example 1 except that 3-(2,3-epoxypropoxy)propyltrimethoxysilane is not added.

[0086] Comparative Example 3

[0087] As a comparative example of Example 1, this example is the same as Example 1 except that tri-bis[4-(3-aminophenoxy)phenyl]ether is not added.

[0088] Example test method:

[0089] 1. Detection method of tensile strength

[0090] Standard: ASTM D638

[0091] Equipment: Universal material testing machine

[0092] 2. Bending strength test method

[0093] Standard: ASTM D790

[0094] Equipment: Universal material testing machine

[0095] Test results:

[0096] Tensile strength MPa Bending strength MPa Example 1 122 184 Example 2 134 198 Example 3 155 222 Example 4 161 227 Comparative Example 1 98 148 Comparative Example 2 117 172 Comparative Example 3 110 165

[0097] Through the above test methods and standards, the high-strength modified engineering plastics prepared by the method of the present invention show significant improvements in tensile strength and flexural strength.

[0098] The applicant declares that the present invention is further illustrated by the above embodiments, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing high-strength modified engineering plastics, characterized in that: The following steps are included: According to weight parts, 50-70 parts of base resin, 3-10 parts of toughening agent, 0.5-2 parts of antioxidant, 0.5-2 parts of lubricant and 0.5-3 parts of plasticizer are added to a high-speed mixer, preliminarily mixed for 5-15 minutes, the machine is stopped to add 10-30 parts of reinforcing fiber, and the mixing is continued for 15-20 minutes. The mixture is extruded through a twin-screw extruder, cooled and cut into particles to obtain the modified engineering plastic; The reinforcing fiber is a modified glass fiber, and its preparation method is: Glass fiber pretreatment: First, clean the glass fiber with a mixture of ethanol and water to remove surface impurities; First step modification: add 2-5 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane to 1000-1200 parts of ethanol, add 100-170 parts of glass fiber, stir at room temperature for 30-60 minutes, and the siloxane group reacts with the surface hydroxyl group of the glass fiber; Second step modification: then add 5-10 parts of bis[4-(3-aminophenoxy)phenyl]ether, 0.03-0.3 parts of trichlorodiethylaminotitanium, 2.2-4.5 parts of 1,5,7-triazabicyclo[4.4.0]dec-5-ene, heat to 60-70°C, and stir for 50-100 minutes; Post-treatment: Finally, filter and dry to obtain surface-modified glass fiber; The matrix resin is selected from polyamide or polycarbonate.

2. The method for preparing a high-strength modified engineering plastic according to claim 1, characterized in that: The toughening agent is selected from at least one of ethylene-propylene-diene monomer rubber, styrene-butadiene rubber, butadiene rubber, thermoplastic polyurethane, thermoplastic polyolefin elastomer, and styrene-butadiene-styrene copolymer.

3. The method for preparing a high-strength modified engineering plastic according to claim 1, characterized in that: The antioxidant is selected from at least one of 2,6-di-tert-butyl-4-methylphenol, pentaerythritol tetrakis[(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, bis[3,5-di-tert-butyl-4-hydroxyphenyl]sulfide, and 2,2'-ethylenebis(4,6-di-tert-butylphenol).

4. The method for preparing a high-strength modified engineering plastic according to claim 1, characterized in that: The lubricant is selected from at least one of zinc stearate, calcium stearate and magnesium stearate.

5. The method for preparing a high-strength modified engineering plastic according to claim 1, characterized in that: The plasticizer is selected from at least one of tri(2-ethylhexyl) phosphate, dioctyl adipate, triethyl citrate, and diisooctyl terephthalate.

6. The method for preparing a high-strength modified engineering plastic according to claim 1, characterized in that: The twin-screw extrusion temperature is 260-280°C.

Citation Information

Patent Citations

  • Environment-friendly and flame retardant PC (polycarbonate) / ABS (acrylonitrile-butadiene-styrene) modified engineering plastic

    CN103467960A

  • Environment-friendly high-modulus PC (Polycarbonate) modified engineering plastic

    CN103467961A

  • High-weather-resistance high-rigidity modified engineering plastic and preparation method thereof

    CN112175383A

  • Specular free-spraying enhanced polycarbonate composition and preparation method thereof

    CN105860488A

  • Special low-temperature-resistant high-speed railway nylon engineering plastic and method for preparing same

    CN108047714A